2007
DOI: 10.1021/jp0756449
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonds in Ionic Liquids Revisited:  35/37Cl NMR Studies of Deuterium Isotope Effects in 1-n-Butyl-3-Methylimidazolium Chloride

Abstract: Detailed knowledge of the structure, dynamics, and interionic interactions of ionic liquids (ILs) is critical to understand their physicochemical properties. In this letter, we show that deuterium isotope effects on the chloride ion 35/37Cl NMR signal represent a useful tool in the study of interionic hydrogen bonds in imidazolium chloride ILs. Sizable Delta35/37Cl(H,D) values obtained for the model system 1-n-butyl-3-methylimidazolium chloride ([C4mim]Cl) upon deuteriation of the imidazolium C-2 and C-2,4,5 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 23 publications
8
70
0
Order By: Relevance
“…36 As a related phenomenon, a direct evidence of the specific hydrogen bonding between H-C(2) and iodide by X-ray crystallography has been reported in the case of 1,3-dialkylimidazolium iodide. 37 Although deuterium exchange of H-C(2) in 1,3-dialkylimidazolium iodide 38,39 and 1-butyl-3-methylimidazolium chloride 25,35 has been reported, it has been reported that the corresponding exchange did not occur in the case where the anion is BF 4 -. 36 The above isotopic exchange was also useful for assigning unique CH-bands of [BMIM][I] in the 3000-3200 cm -1 range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 As a related phenomenon, a direct evidence of the specific hydrogen bonding between H-C(2) and iodide by X-ray crystallography has been reported in the case of 1,3-dialkylimidazolium iodide. 37 Although deuterium exchange of H-C(2) in 1,3-dialkylimidazolium iodide 38,39 and 1-butyl-3-methylimidazolium chloride 25,35 has been reported, it has been reported that the corresponding exchange did not occur in the case where the anion is BF 4 -. 36 The above isotopic exchange was also useful for assigning unique CH-bands of [BMIM][I] in the 3000-3200 cm -1 range.…”
Section: Resultsmentioning
confidence: 99%
“…The big disparity in isotopic exchange rate between [BMIM] [BF 4 ] and [BMIM][I] also corroborates that the relative position of the anion is different. 35,36,38 Study of this RIL + water mixture system with vibrational spectroscopy helped since it was possible to infer the bulk structure of the ionic liquid from the gradual changes in the vibrational spectra with varying water content. The spectra for [BMIM][BF 4 ] + water mixtures did not change appreciably other than the decrease in the overall peak strength due to the From the observed spectra in the 3000-3200 cm -1 range, we propose the BF 4 -anion is symmetrically positioned around the top of the imidazolium core for pure [BMIM][BF 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the labile nature of the imidazolium protons, the preparation of these isotopologues only requires an H/D exchange of the IL with D 2 O, either pure or in the presence of a weak base. 2,6 In order to use established literature methods, 6,7 the synthesis of [C 4 mim]Cl bearing sequential labels along the N-alkyl groups requires suitable deuterated 1-chlorobutane precursors. While similar compounds have been reported in the literature, their preparation employed relatively low-yielding reactions and expensive starting materials which are no longer commercially available.…”
Section: Resultsmentioning
confidence: 99%
“…Cl X-ray, [31] IR, [61] NMR, [62] neutron [53] CÀH···ClA C H T U N G T R E N N U N G (Br, I) 0.44 [g] 378.03 84 285…”
Section: Dementioning
confidence: 99%